Epidemiologic profile of oral squamous cell carcinoma in Yogyakarta, Indonesia - Gracia, Isadora; Utoro, Totok; S., Supriatno; Astuti, Indwiani; Heriyanto, Didik Setyo; Pramono, Dibyo (Padjadjaran Journal of Dentistry, 2017)
ABSTRACTIntroduction: Oral cancer is a major health problem in the world, indicated by a high incidence of recurrence. In Southeast Asia, oral cancer ranks sixth from all cancers on the human body. The incidence of oral cancer, especially squamous cell carcinoma types, increases every year, but the prognosis and patients life expectancy are still unsatisfying enough and the reports about the profile of oral cancer is still limited.The objective of this research was to get the epidemiological profile of oral squamous cell carcinoma (OSCC) in Yogyakarta, Indonesia. Methods: The research method was observational analytic with cross-sectional design. All new OSCC cases in three anatomic pathology laboratory installations in Yogyakarta (January 2011-December 2015) were included in this study. Data collected were gender, age, anatomical location, and histology. All data were analyzed using statistical analysis program. Results: OSCC new cases amount increasing each year: 6 cases (6.6%) in 2011, and increased to 24 cases (26.4%) in 2015. Fifty-two of the 91 cases (57.1%) were found on male. The age group with the most cases was found in group of 41-60 years (49.5%). There is no difference in the case distribution by age between male and female. Forty-eight cases were found in the lingual part (52.7%). Histological examination showed 68 cases (74.7%) were well-differentiated carcinoma. Conclusion: OSCC profile in Yogyakarta mostly found in men with anatomical location in the lingual part in the age group above 40 years of age and were having well-differentiated histology.Keywords: Oral squamous cell carcinoma (OSCC), Epidemiologic profile, Yogyakarta